Observation of atmospheric microplastic accumulation in lichen xanthoria parietina thallus using fluorescent techniques - ÇOBANOĞLU, GÜLŞAH (My University, 2023)
The ever-increasing plastic pollution is one of the most important environmental problems of our time. Plastic products and their wastes contain many harmful substances within the scope of permanent organic pollutants (POPs), especially microplastics. Microplastic pollution, which is concentrated in water, land, and air, especially in urban and industrial areas, has various negative effects on all living organisms in natural habitats. Polluted air, including invisible microplastics, causes serious health problems such as shortness of breath and cancer in humans. In this study, it was aimed to determine the presence of atmospheric microplastics in Istanbul with biomonitor lichens, known as a biological monitoring tool for airborne pollutants. Epiphytic foliose lichen Xanthoria parietina was sampled from natural areas within the city limits. The surface and anatomical sections of thalli of 11 lichen samples and the reference material were examined by Nile Red staining technique under fluorescent microscope by comparison with the reference lichen material. The yellow glowing MP particles were determined by fluorescent technique are shown with microscope visuals. According to determinations by fluorescence microscopy analysis that the lichens can accumulate microplastic particles in the air. Although microplastic accumulation is in all areas, it was determined that the most concentrated in lichen samples from Beykoz and the least in Maltepe districts. It is thought that the source of atmospheric microplastic pollution in urban woodlands may be due to anthropogenic factors or the transport of wastes in industrial areas to long distances. This study is one of the newest biomonitoring studies aimed at detecting airborne microplastics with lichens.